2014
DOI: 10.4314/njp.v41i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Causes of stillbirth in a community survey in Gombe State

Abstract: Background: Perinatal mortality rate is very high in North Eastern Nigeria mainly due to a large number of still births. The causes and factors related need to be identified so as to proffer solutions with a view to improving obstetric practice and perinatal survival. Objectives: To identify the causes and factors related to stillbirths in Dukku Local Government Area of Gombe state. Methodology: A prospective study that was both hospital and community based, in which parturients were recruited in their last tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 2 publications
(4 reference statements)
3
11
0
Order By: Relevance
“…Delivering at health center rather than delivering at home brought about less probability to experience stillbirth. This finding was consistent with a prospective study entitled ’Causes of stillbirth in a community survey in Gombe State’, Nigeria [ 24 ]. This happens because when mothers deliver at home, they might not find skilled attendant and in difficult case there is no other choice like caesarean section in health centers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Delivering at health center rather than delivering at home brought about less probability to experience stillbirth. This finding was consistent with a prospective study entitled ’Causes of stillbirth in a community survey in Gombe State’, Nigeria [ 24 ]. This happens because when mothers deliver at home, they might not find skilled attendant and in difficult case there is no other choice like caesarean section in health centers.…”
Section: Discussionsupporting
confidence: 92%
“…For older women, stillbirth risk rises more rapidly as gestational age increases beyond 37 weeks. A prospective study done in Nigeria also revealed that 35 years and above pregnancy was important factor contributing to high stillbirth rate [ 24 ]. And almost all researchers in the literature agree in that advanced maternal age is contributing factor to high stillbirth rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was consistent with a prospective study entitled 'Causes of stillbirth in a community survey in Gombe State', Nigeria. 30 This happens because when mothers deliver at home, they might not find skilled attendant and in difficult case there is no other choice like caesarean section in health centers.…”
Section: Discussionmentioning
confidence: 99%
“…29 A research finding also revealed that lack of antenatal care had positive association with stillbirth. 30 In the binary logistic analysis done in Hawassa University Hospital, southern Ethiopia, both the crude and adjusted analysis showed that the stillbirth rate was highest among mothers who had no ANC follow up. 31 The best model of the study, random intercept model, found also that place of delivery was significant factor for experiencing stillbirth.…”
Section: Discussionmentioning
confidence: 99%